Effects of school, family, social interactions on dropout rate among secondary school students - Azlina Binti Abdullah, Waleed Mohammed Alabdulrazaq, Mimi Hanida Abdul Mutalib, (Opción, 2020)
A qualitative study was conducted to evaluate major factors affecting male students’ dropout through interviews conducted on a selected sample of 360 respondents in Saudi Arabia. Results showed that school-related factors and social interactions had significant relationships with dropout rate, recording a P-value of less than 5% level of significance. The coefficient for availability of school facilities of -0.355 suggests a decrease in dropout rate. A 1% increase tended to decrease the rate by 0.355%. In conclusion, the availability of jobs and social discrimination can further increase school enrolment and reduce dropout rates which the government and stakeholders should undertake.